Trans-trigeminal transport of masseter-derived neprilysin to hippocampus. (October 2020) - Kuwajima, Yukinori; Nagai, Manavi S.; Lee, Cliff; Galaburda, Albert M.; Kobayashi, Takuya; Nakasato, Ayaka; Da Silva, John D.; Nagai, Shigemi Ishikawa; Nagai, Masazumi
Highlights: Neprilysin was transported from masseter muscle to hippocampus via trigeminal nerve. Masseter muscle-injected exosomes travelled to hippocampus via trigeminal nerve. Neprilysin is an exosomal cargo. Masseter muscle-trigeminal nerve-hippocampus can be an exosomal drug delivery routeshow. Abstract: Objective: To show the possible occurrence of exosomal transport of neprilysin from masseter muscle to hippocampus via trigeminal nerve in the living mouse. Design: Mouse C2C12 myotube-derived exosomes were labeled with near-infrared (NIR) dye and injected into the masseter muscle to track their fluorescence from masseter muscle to hippocampus via trigeminal nerve. A plasmid vector encoding green fluorescent protein (GFP)-tagged neprilysin (GFP-neprilysin) was transfected into masseter muscle of C57BL/6 J mice. Expression of mRNA and encoded protein of the transgene was identified in masseter muscle, trigeminal nerve and hippocampus by RT-PCR and Western blot, respectively. Results: Peak of exosomal NIR in masseter muscle at time 0 rapidly reduced at 3 h and 6 h along with the subsequent increases in trigeminal nerve and hippocampus. Expression of GFP-neprilysin mRNA was detected in masseter muscle, but not trigeminal nerve and hippocampus. On the other hand, the corresponding protein of GFP-neprilysin was identified in the three tissues on day 3 after transfection into masseter muscle as a single band on Western blots with anti-GFP and anti-neprilysin antibodies. Conclusion: The appearance of GFP-neprilysin protein in trigeminal nerve and hippocampus without a corresponding mRNA expression indicated the protein's origin from the masseter muscle. Concomitant migration of NIR-exosomes from masseter muscle to hippocampus via trigeminal nerve suggested the possible occurrence of exosomal transport of neprilysin.